2022
DOI: 10.3390/ijms23073623
|View full text |Cite
|
Sign up to set email alerts
|

CRPC Membrane-Camouflaged, Biomimetic Nanosystem for Overcoming Castration-Resistant Prostate Cancer by Cellular Vehicle-Aided Tumor Targeting

Abstract: Castration-resistant prostate cancer (CRPC) is the most common malignant tumor of the male urinary system. Nanodrug delivery systems (NDDS) have been widely applied in drug delivery for tumor therapy; however, nanotherapeutics encounter various biological barriers that prevent successful accumulation of drugs, specifically at diseased sites. Therefore, there is an urgent need to develop a CRPC-targeting nanocomposite with fine biocompatibility for penetrating various biological barriers, delivering sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As chemotherapeutic drugs are readily eliminated by tumor cells [ 53 ], it is crucial to prolong drug retention within tumor cells. After 72 h of coincubation with DC, DC/Pep2 and DC/Pep1, confocal microscopy detected the red fluorescence of DOX and the green fluorescence of CUR in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…As chemotherapeutic drugs are readily eliminated by tumor cells [ 53 ], it is crucial to prolong drug retention within tumor cells. After 72 h of coincubation with DC, DC/Pep2 and DC/Pep1, confocal microscopy detected the red fluorescence of DOX and the green fluorescence of CUR in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, two differently sized FL-SiO 2 NPs, FL-SiO 2 NPs-0 nm and FL-SiO 2 NPs-150 nm, were prepared using surfactant CTAB as a structure-directing agent, with TEOS used as a silica precursor. The carbon dots formed during the calcination process in preparation of FL-SiO 2 NPs produce the stable and strong fluorescence which is essential for in vivo imagining of nanoparticles as delivery vehicles in biological systems [ 48 , 49 , 50 ]. Methoxyfenozide was loaded into FL-SiO 2 NPs by simple immersion in a CH 3 OH solution by magnetically stirring at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…reported that the uptake of membrane‐coated nanoparticles in human breast cancer MDA‐MB‐435 cells was increased by 20‐fold compared to naked nanoparticles. 102 Many studies have demonstrated the selectivity and biosafety of cancer cell membrane‐based biomimetic nanoparticles using in vitro and in vivo MDR cancer models, 103 , 104 , 105 suggesting a novel drug delivery strategy to improve therapeutic efficacy for MDR cancer.…”
Section: Resistance Mechanisms In Cancer and Combating Strategiesmentioning
confidence: 99%